1986
DOI: 10.1002/cjce.5450640204
|View full text |Cite
|
Sign up to set email alerts
|

Developing and fully developed turbulent flow of drag reducing fluids in an annular duct

Abstract: Velocity profiles for the inner and outer flow regions of annuli are proposed for the turbulent flow of drag reducing fluids. Theoretical expressions for friction factors are developed. From the shear stress equations and the velocity profiles, estimates for the entrance lengths are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…30,31 Figure 10 and Tables 1 and 2 show that the presence of polyox drag-reducing polymer decreases the mass-transfer coefficient of the diffusion-controlled corrosion in the inlet jet zone of the annulus by an amount ranging from 29.95% to 68.86% depending on polymer concentration, electrolyte concentration, and inlet nozzle diameter. Unlike other cases, such as drag reduction in fully developed flow in tubes and annuli, [17][18][19][20][21] the % reduction in K shown in Tables 1 and 2 is not sensitive to Re. Previous studies conducted in tubes under fully developed flow have shown that the % drag reduction or % decrease in K increases with Re; owing to the increase in the degree of stretching of polymer molecules under the influence of the shear stress, 35 the higher the degree of stretching of the polymer molecules, the higher is their ability to dampen the small-scale, high-frequency eddies.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…30,31 Figure 10 and Tables 1 and 2 show that the presence of polyox drag-reducing polymer decreases the mass-transfer coefficient of the diffusion-controlled corrosion in the inlet jet zone of the annulus by an amount ranging from 29.95% to 68.86% depending on polymer concentration, electrolyte concentration, and inlet nozzle diameter. Unlike other cases, such as drag reduction in fully developed flow in tubes and annuli, [17][18][19][20][21] the % reduction in K shown in Tables 1 and 2 is not sensitive to Re. Previous studies conducted in tubes under fully developed flow have shown that the % drag reduction or % decrease in K increases with Re; owing to the increase in the degree of stretching of polymer molecules under the influence of the shear stress, 35 the higher the degree of stretching of the polymer molecules, the higher is their ability to dampen the small-scale, high-frequency eddies.…”
Section: Resultsmentioning
confidence: 76%
“…These polymers proved to be effective in reducing mass-transfer- and diffusion-controlled corrosion in pipelines , and agitated vessels 7,8 operated under turbulent flow. Drag-reducing polymers have the potential of being used in annular equipment operating under turbulent flow to reduce pumping power consumption by virtue of the ability of polymer molecules to dampen the small-scale, high-frequency energy dissipating eddies which prevail in the buffer sublayer of the hydrodynamic boundary layer. , Polyox WSR−301 (polyethelene oxide), a product of Union Carbide, was used in the present work in the form of a slurry rather than a solution to minimize mechanical degradation of the polymer molecules as recommended by Little et al…”
Section: Introductionmentioning
confidence: 99%
“…Equation (1 8) has been used when analyzing turbulent flow in horizontal pipes by Shenoy and Mashelkar (1983), in curved tubes by Shenoy et al (1980), in rotating straight tubes by Shenoy (1986), in annular ducts by Shenoy and Shintre (1986) and in vertical tubes by Shenoy (1987).…”
Section: And the Stanton Numbermentioning
confidence: 99%